Kepentingan Umum sebagai Pengecualian pada Tindak Pidana Pencemaran Nama Baik dalam Undang-Undang Informasi dan Transaksi Elektronik - Daniela Sine, Elena; Parabandani, Hendra Wahanu (FOCUS, 2025)
The advancement of science and technology has led to the emergence of new societal frameworks, enabling the rise of new legal actions. Law Number 1 of 2024 on the Second Amendment to Law Number 11 of 2008 on Information and Electronic Transactions, was established as a response to the legal need for regulations governing actions in electronic media, particularly concerning defamation. The regulation of "public interest" as an exception to criminal acts warrants deeper examination to ensure justice, certainty, and the utility of law. This study employs a normative legal research methodology aimed at developing arguments, theories, and concepts to address legal issues. The approaches utilized include legislative, conceptual, and analytical methods. The findings indicate that determining the public interest aspect in defamation cases involves several evaluative criteria: intent, substance, and impact. This research aims to delineate the appropriate aspects and perspectives for assessing public interest, thereby promoting justice, certainty, and the utility of law.